The effect of combined probiotics with catalyst supplementation on digestion and rumen characteristic in Priangan sheep - Krisnan, Rantan; Haryanto, Budi; Wiryawan, Komang G. (Indonesian Journal of Animal and Veterinary Sciences, 2009)
An experiment was carried out to investigate the effect of combined supplementation of probiotics and catalyst on digestion and rumen characteristic in Priangan sheep. The trial was conducted using 16 heads of young male Priangan sheep with average initial weight of 18 kg in completely randomized design with factorial 2x2 and 4 replication. The first factor was two types of probiotics mixed with catalyst supplement, while the second factor was two levels of supplement percentage of catalyst at 0.5 and 1.0% of concentrate. The type of probiotics applied was probion and probiotics of buffaloes rumen microbes. The feeding level was set at 3% of body weight based on dry matter and consisting of forage (King grass) and concentrate at 50:50 ratio. The results indicated a significantly greater fibre digestion value (NDF) and proportion of acetate molar in the group of sheep fed combination of probiotics of buffaloes rumen microbes and catalyst supplement. It was concluded that the recommendation level of the combined rumen microbe probiotics with catalyst supplement in sheep ration was 0.5%. Key words: Probiotic-Catalyst Supplement, Digestibiliy, Rumen Characteristic, Sheep